Data update on anthrax stationary hazardous areas and soil foci as a basis for improving epizootological and epidemiological monitoring for anthrax in the Russian Federation - Anna Yu. Popova; Alexander N. Kulichenko; Vasiliy G. Akimkin; Sergey V. Balakhonov; Fedor V. Logvin; Alla G. Ryazanova; Diana K. Gerasimenko; Marina N. Loktionova; Tatiana A. Chekanova; Zorigma F. Dugarzhapova; Anna V. Nikitina; Kseniya A. Oleynikova; et al. (Журнал микробиологии, эпидемиологии и иммунобиологии)
Introduction. Anthrax is registered annually in the Russian Federation. The constant risk of complication of the epizootological and epidemiological situation on anthrax is due to the widespread distribution of soil foci of infection (anthrax burials (AB), «pestilence fields») and associated stationary hazardous areas (SHA).